2017
DOI: 10.1002/ehf2.12165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles and prognosis of acute heart failure in adult patients with dystrophinopathies on home mechanical ventilation

Abstract: AimsDuchenne muscular dystrophy (DMD) is characterized by respiratory and heart involvements. In the context of permanently wheelchair bound and on mechanical ventilation (MV) patients, the clinical presentation of acute heart failure (AHF) syndrome may be atypical. We sought to describe clinical and genetic profiles and to determine prognosis of DMD and Becker muscular dystrophy (BMD) patients on home MV (HMV), hospitalized for AHF.Methods and resultsWe included genetically proven DMD and BMD patients on HMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…16 Other non-cardiac factors may increase modestly the BNP level, including chronic obstructive pulmonary disease, pulmonary embolism, pulmonary hypertension, pneumonia, atrial fibrillation, acute coronary syndrome. 17 However, in our study, median BMI was 19 kg/m 2 and gender was mainly male. No patient experienced chronic renal failure.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…16 Other non-cardiac factors may increase modestly the BNP level, including chronic obstructive pulmonary disease, pulmonary embolism, pulmonary hypertension, pneumonia, atrial fibrillation, acute coronary syndrome. 17 However, in our study, median BMI was 19 kg/m 2 and gender was mainly male. No patient experienced chronic renal failure.…”
Section: Discussioncontrasting
confidence: 62%
“…Cardiac symptoms are subtle and nonspecific 1 and the presence of mechanical ventilation may provide respiratory clinical picture modifications. 2 In this difficult clinical context, biomarkers could represent an interesting tool to help bedside decision making. Brain natriuretic peptide (BNP) is a 32-amino acid protein produced and released by the heart ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we showed that cardiac phenotypic severity is determined by the age at onset of LVD. Even with cardiac medications and assisted ventilation, the slope in the decline in SF did not differ between patients with the milder cardiac phenotype (onset of LVD at age ≥ 18 years) compared to patients with the severe cardiac phenotype (onset of LVD at age < 18 years) More acutely, DMD patients who have progressed to CHF have been shown to have very poor survival, even when treated with chronic mechanical ventilation and cardiac medications, with an intrahospital mortality rate of 30% in one study, reaching almost 54% after 1 year 23 . Similarly, we found that despite treatment with cardiac medications and assisted ventilation, mean survival was just 8 months in our DMD patients once they developed CHF 15 …”
Section: Phenotypic Discordance and Patient Prognosismentioning
confidence: 87%
“…It has been shown in two previous studies that bed rest and limited activity are detrimental to exercise tolerance and aerobic capacity while exercise training improves vasodilatation and muscle oxidative capacity in patients with HF. [ 25 26 ]…”
Section: Discussionsmentioning
confidence: 99%